OLAHRAGA SEBAGAI MEDIA PENGUATAN NILAI PENDIDIKAN KARAKTER MELALUI PROGRAM SENAM ANAK INDONESIA HEBAT (Indonesia Sport Journal, 2025)
This study aims to examine the implementation of the Great Indonesian Children's Gymnastics Program (AIH) as a means of character building at SDN 2 Kalipuro. This program is carried out routinely every Thursday and Saturday morning, and intensively before the sub-district gymnastics competition, where the school won 3rd place. This study uses a descriptive qualitative approach with the subjects being the principal and students. Data collection techniques are carried out through observation, interviews, and documentation. The results of the study indicate that AIH gymnastics not only improves physical fitness, but also instills character values ​​such as discipline, hard work, sportsmanship, religiosity, and love for the country. Gymnastics activities accompanied by music with nuances of Indonesian culture and the national anthem in the cool-down session strengthen students' nationalism. Thus, AIH gymnastics has proven to be an effective medium in strengthening character education in elementary schools.